ЗНИЖЕННЯ ПУЛЬСАЦІЙ ОБЕРТОВОГО МОМЕНТУ БЕЗПАЗОВОГО МОМЕНТНОГО ДВИГУНА З ПОСТІЙНИМИ МАГНІТАМИ ШЛЯХОМ ВИКОРИСТАННЯ ДВОШАРОВОЇ ОБМОТКИ - Пєтухов, І.С.; Кіреєв, В.Г.; Акінін, К.П.; Лавриненко, В.А. (Інститут електродинаміки НАН України, Київ, 2024)
The torque of a magnetoelectric torque motor with surface-mounted permanent magnets on the rotor was studied. The sinusoidal current supply mode is considered. The torque was calculated according to the static model of the magnetic field. It was determined that the third harmonic makes a significant contribution to the torque ripple. To reduce the third harmonic it is proposed to use a winding with a shortened pitch, for which it is necessary to make this winding in two layers. The optimal values of the number of pole pairs, the angular width of the magnets of the magnetic field excitation system, and the shortening of the winding pitch were determined. It was found that shortening of the winding pitch decreases the torque ripple by 2 ... 2.5 times. References 7, figures. 6, tables 3.